2013
DOI: 10.1111/aji.12172
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Ashwagandha (Withania somnifera, Dunal) Enhances NK Cell Function in Ovarian Tumors in the Laying Hen Model of Spontaneous Ovarian Cancer

Abstract: The results of this study suggest that the population of stromal and tumorinfiltrating NK cells is increased by dietary Ashwagandha supplementation. Thus, Ashwagandha may enhance antitumor function of NK cells. This study may be useful for a clinical study to determine the effects of dietary Ashwagandha on NK cell immune function in patients with ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Another study conducted in hens susceptible to ovarian cancer development showed that ashwagandha supplementation reduced the incidence of tumor development; changes in NK cell population were also observed. Both stromal and intratumoral NK cell populations significantly increased after supplementation, suggesting a protective function of NK cells against carcinogenesis [83]. The influence of ashwagandha extracts on NK cells requires both the identification of an active compound in the extracts and further studies on its mechanism of action.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Another study conducted in hens susceptible to ovarian cancer development showed that ashwagandha supplementation reduced the incidence of tumor development; changes in NK cell population were also observed. Both stromal and intratumoral NK cell populations significantly increased after supplementation, suggesting a protective function of NK cells against carcinogenesis [83]. The influence of ashwagandha extracts on NK cells requires both the identification of an active compound in the extracts and further studies on its mechanism of action.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…ovarian cancer (39). This finding suggests that ashwagandha may enhance the antitumor function of natural killer cells.…”
Section: The Chicken: the Perfect Animal Model To Study Human Ovarianmentioning
confidence: 80%
“…Despite all research focused towards WA formulation as an anticancer drug, Barua et al (2013) have focused on the direct application of W. somnifera, in the form of powder obtained from root, into the diet of hen for the study of natural killer cells function in ovarian tumors. For this, plant root powder was supplemented in the diet of hen continuously for 90 d and compared it with control (hens that were not supplemented with W. somnifera root powder in their diet) and examined for the stromal natural killer cells with intratumoral natural killer cells of ovarian cancer.…”
Section: Withaferin a (Wa)mentioning
confidence: 99%